Carbon Sources Application Increase Wheat Yield and Soil Fertility. Issue 7 (12th April 2021) - Imran,; Amanullah,; M. Al-Tawaha, Abdel Rahman
ABSTRACT: Soil organic matter and especially soil carbon is one the major component of soil health to sustain crop productivity and soil sustainability. The objectives of this study were to evaluate the most promising organic source for the highest wheat yield production and its impact on soil quality. This study was conducted to evaluate the effect of charcoal and compost on wheat yield and soil quality parameters. The experiment was conducted at Matta Circle as a wheat demonstration plot for the farmers of Matta Tehsil during the Rabi season of 2011–2012. The variety used was PIRSABAQ-2004. The experiment was laid down Randomized Complete Block Design (RCBD) with three replications, each replication with five treatments. The soil physicochemical characteristics were greatly influenced by charcoal and compost combine application. The results obtained from the study revealed that more tillers plant −1, number of productive tillers, promising number of grain spike −1, and 1000 grain weight was recorded with combine application of Compost and Charcoal @ 5 + 5 Mg ha −1 whereas highest biological yield and grain yield were noted with compost application @ 10 Mg ha −1 . The tallest plants were produced with 10 Mg ha −1 charcoal application as compared to the combined application of compost + charcoal + inorganic fertilizers. We concluded that combined application of organic (charcoal + compost) and inorganic (NPK) fertilization could be promising in attaining high yields with the advantage of improved soil physicochemical characteristics of the soil to maintain the soil health, sustainability, soil productivity, and ultimately food security and increased yields.